Development and preliminary validation of the Parent Efficacy for Child Healthy Weight Behaviour Scale. (February 2013) - Nelson, Marina; Davis, Melissa Christine
This study developed a new measure of parent self-efficacy for promoting healthy weight behaviours in their children, the Parent Efficacy for Child Healthy Weight Behaviour Scale (PECHWB). In total 601 primary caregivers of children aged 4–17 completed an online survey consisting of the PECHWB, a measure of general parenting self-efficacy, measures of parental depression, anxiety and stress and demographic questions. Factor analysis identified four PECHWB subscales with high levels of internal consistency. The PECHWB showed significant small positive correlations with a measure of global parenting self-efficacy and small negative correlations with measures of parental negative affect. This study provides initial evidence for the reliability and validity of the PECHWB. Future research is required to establish further evidence of the psychometric properties of the PECHWB scale in independent samples before the scale can be used in evaluating intervention outcomes.